Effect of Toxicity Concentration of Waste Lubricating Oil (Hazardous Noxious Substances) on Aquatic Life - Munirah Bt Abdullah, Nor; Sabiha binti Mohd Aluwi, Nur; Park, Heekyung; binti Ahmad Kamal, Norashikin (International Journal of Engineering and Technology, 2018)
This lab scale study aims to investigate the effect of different concentration of waste lubricating oil on the African catfish juveniles, Clarias gariepinus. Five different concentrations of waste lubricating oil were used for 96 hours period which are 0 ml/L, 5 ml/L, 10 ml/l, 15 ml/l, and 20 ml/L. After 96 hours of experiment, tank 4 which being added with 20 mL waste lubricating oil shows the highest percentage of fish mortality (100%) followed by tank 3 (95%), and tank 2 (76%) while the lowest percentage of mortality is recorded in tank 1 (19%). The result from the toxicity test showed that the higher the concentration of waste lubricating oil, the higher the mortality rate of fish.Â The lethal concentration LC50 that caused 50% mortality of test fish was estimated at 8.1 ml/L. From the observation, waste lubricating oil which contains heavy metals had cause damage to renal and nervous system of fishes thus causing them to lost equilibrium and irregular vertical swimming that will finally cause death. It can be concluded that the harmful environment that will trigger death of fish will be created by indiscriminate discharge of waste oil into water bodies. Therefore, it is recommended to treat the wastewaters, sewage and industrial wastes before it is being discharged into the aquatic ecosystems to sustain the aquatic species for the future.Â The proper effluent treatment technology should be adopted to check the present of oil spillage in the water. The enforcement of laws and legislations related to the protection of aquatic environment must be enhance and take into considerations.Â